Out Come of Modified Duhamel Procedure for Hirschsprungs Disease in Sheikh Zayed Hospital Rahim Yar Khan (Journal of Fatima Jinnah Medical University, 2018)
Hirschsprung’s Disease (HD) is a congenital condition, which is characterized by the absence of Ganglion cells in submucosal (Meissner’s) plexus and the intermuscular (Auerbach’s) plexus.Aim: To determine the outcome of modified Duhamel procedure in sheikh zayed hospital Rahim yar khanDesign: This is case series study.Settings: Department of Pediatric Surgery Sheikh Zayed Medical College Rahim Yar KhanPeriod: Seventeen cases were operated from 20th December 2012 to 20th may 2014.Material and Method: Seventeen (17) cases from both sexes were operated for Hirschsprung's Disease. All patients were diagnosed cases of rectosigmoid aganglionosis and followed up for a period of one year according to comprehensive Performa. Four parameters like normal stool evacuation, abdominal distention, soiling and stool incontinence were followed then the results were compared with other national and international studies.Results: fever 23.5% (n=04), wound infection 23.5% (n=04), vomiting 11.76% (n=02), abdominal distension 5.8% (n=01), and bleeding per5.8% (n=01), were the immediate post operative complications. Abdominal distention was observed occasionally in six patients (35.2%). Soiling was seen in five patients (29.41%). Out of Seventeen, stool incontinence was seen in only three patients.Conclusion: Modified Duhamel Procedure with the help of linear cutter stapler device is quite safe & less time consuming. Infact (Modified Duhamel) is the procedure of choice for Hirschsprung's Disease these days.
Keywords: Hirschsprung'sDisease Modified Duhamel Procedure, Constipation, Soiling, Mechanical Stapling Device.